Deep ploughing increases agricultural soil organic matter stocks. (1st June 2016) - Alcántara, Viridiana; Don, Axel; Well, Reinhard; Nieder, Rolf
Abstract: Subsoils play an important role within the global C cycle, since they have high soil organic carbon (SOC) storage capacity due to generally low SOC concentrations. However, measures for enhancing SOC storage commonly focus on topsoils. This study assessed the long‐term storage and stability of SOC in topsoils buried in arable subsoils by deep ploughing, a globally applied method for breaking up hard pans and improving soil structure to optimize crop growing conditions. One effect of deep ploughing is translocation of SOC formed near the surface into the subsoil, with concomitant mixing of SOC‐poor subsoil material into the 'new' topsoil. Deep‐ploughed croplands represent unique long‐term in situ incubations of SOC‐rich material in subsoils. In this study, we sampled five loamy and five sandy soils that were ploughed to 55–90 cm depth 35–50 years ago. Adjacent, similarly managed but conventionally ploughed subplots were sampled as reference. The deep‐ploughed soils contained on average 42 ± 13% more SOC than the reference subplots. On average, 45 years after deep ploughing, the 'new' topsoil still contained 15% less SOC than the reference topsoil, indicating long‐term SOC accumulation potential in the topsoil. In vitro incubation experiments on the buried sandy soils revealed 63 ± 6% lower potential SOC mineralisation rates and also 67 ± 2% lower SOC mineralisation per unit SOC in the buried topsoils than in the reference topsoils. Wider C/N ratio in the buried sandy topsoils than in the reference topsoils indicates that deep ploughing preserved SOC. The SOC mineralisation per unit SOC in the buried loamy topsoils was not significantly different from that in the reference topsoils. However, 56 ± 4% of the initial SOC was preserved in the buried topsoils. It can be concluded that deep ploughing contributes to SOC sequestration by enlarging the storage space for SOC‐rich material.